USING STORYTELLLING TO ENHANCE STUDENTS’ INTERESTS IN READING - Eka Rianty Anggraini (Journal of English Education Program (JEEP), 2021)
This research explores the use of storytelling to enhance students interests in reading. It was argued that the use of storytelling would provide students with the powerful tool used in the classroom. A case study methodology was used in this research and this research was conducted at the tenth grade of Vocational School in A Regency. It took an English Teacher who teaches reading class and 35 students as samples who were chosen by purposive sampling. The conclusion of the study shows that the implementation of storytelling is conducted by practice storytelling and teacher’s perception and students’ responses shows that storytelling can enhance students’ reading in classroom. Based on these research findings, it is recommended that the teacher can use storytelling in teaching reading to Senior High School students. Furthermore, the storytelling enhances students in reading. Keywords: interest, reading, reading comprehension, reading skill, storytelling